2019
DOI: 10.1111/cobi.13241
|View full text |Cite
|
Sign up to set email alerts
|

Governing trade‐offs in ecosystem services and disservices to achieve human–wildlife coexistence

Abstract: Sustaining wildlife populations, which provide both ecosystem services and disservices, represents a worldwide conservation challenge. The ecosystem services and Ostrom's social–ecological systems frameworks have been adopted across natural and social sciences to characterize benefits from nature. Despite their generalizability, individually they do not include explicit tools for addressing the sustainable management of many wildlife populations. For instance, Ostrom's framework does not specifically address c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
75
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 56 publications
2
75
0
Order By: Relevance
“…Several studies provide an excellent foundation for enumerating and refining those factors (Lischka et al 2018). Our findings on how different social and ecological characteristics led to differential research interest on ecosystem services and conflicts supports previous calls to apply social-ecological approaches in order to uncover the multiple beneficial and detrimental contributions provided by carnivores to people (Ceausu et al 2018, Lozano et al 2019, Jones et al 2019.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Several studies provide an excellent foundation for enumerating and refining those factors (Lischka et al 2018). Our findings on how different social and ecological characteristics led to differential research interest on ecosystem services and conflicts supports previous calls to apply social-ecological approaches in order to uncover the multiple beneficial and detrimental contributions provided by carnivores to people (Ceausu et al 2018, Lozano et al 2019, Jones et al 2019.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, ecosystem services provided by carnivores were reported only in 38% of articles. Neglecting ecosystem services provided by carnivores, both in scientific research and outreach activities, can undermine attempts to foster human tolerance for carnivores, which is a critical component of coexistence (Peterson et al 2010, Pooley et al 2017, Ceausu et al 2018, Lozano et al 2019. Therefore, we call for a shift in mindset that recognizes the dual role of carnivores as providers of both ecosystem services and disservices to humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evaluating spatial patterns of ecosystem services, disservices, and their recipients Researchers also seek to quantify and map ecosystem services provided by wildlife, such as ecotourism, crop pollination, or waste and pest removal (Lozano et al 2019). In other instances, wildlife can be the source of ecosystem disservices or conflicts, such as crop damage or livestock depredation (Ceauşu et al 2019). However, a recent global assessment found that current research has emphasized conflicts in lieu of taking into account both benefits and costs of wildlife (Lozano et al 2019).…”
Section: Integrating Social Dynamics Into Habitat Assessmentsmentioning
confidence: 99%
“…The socio-ecological 324 implications of some species' recolonising part of their historical range or occupying new areas should be 325 carefully considered, in particular for species often involved in human-wildlife conflicts, such as large 326 carnivores [82]. Unified socio-ecological approaches that explicitly acknowledge competing perspectives 327 between wildlife conservation and social and governance contexts can be applied to provide new insights 328 into management options for sustainable human-wildlife coexistence [83]. 329 6.…”
Section: Potential Refugia 311mentioning
confidence: 99%